Karnataka Annual Plan 1982-83 Volume-IV Special Component Plan for the Welfare of Scheduled Castes - Planning Commission (Planning Commission, 1982)
The promotion with special care of the educational economic and social interests of the Scheduled Castes has always been an integral part of all development effort in Karnataka. The effective implementation of the 20 point economic programme, Employment Affirmation scheme, the Social Welfare Department’s massive programmes for their growth and Special programmes for Rural Development like S.F.D.A. bear ample testimony to this.
Planning Department, Government of Karnataka